Land Use Change Increases Streamflow Across the Arc of Deforestation in Brazil. Issue 8 (26th April 2018) - Levy, M. C.; Lopes, A. V.; Cohn, A.; Larsen, L. G.; Thompson, S. E.
Abstract: Nearly half of recent decades' global forest loss occurred in the Amazon and Cerrado (tropical savanna) biomes of Brazil, known as the arc of deforestation. Despite prior analysis in individual river basins, a generalizable empirical understanding of the effect of deforestation on streamflow across this region is lacking. We frame land use change in Brazil as a natural experiment and draw on in situ and remote sensing evidence in 324 river basins covering more than 3 × 10 6  km 2 to estimate streamflow changes caused by deforestation and agricultural development between 1950 and 2013. Deforestation increased dry season low flow by between 4 and 10 percentage points (relative to the forested condition), corresponding to a regional‐ and time‐averaged rate of increase in specific streamflow of 1.29 mm/year 2, equivalent to a 4.08 km 3 /year 2 increase, assuming a stationary climate. In conjunction with rainfall and temperature variations, the net (observed) average increase in streamflow over the same period was 0.76 mm/year 2, or 2.41 km 3 /year 2 . Thus, net increases in regional streamflow in the past half century are 58% of those that would have been experienced with deforestation given a stationary climate. This study uses a causal empirical analysis approach novel to the water sciences to verify the regional applicability of prior basin‐scale studies, provides a proof of concept for the use of observational causal identification methods in the water sciences, and demonstrates that deforestation masks the streamflow‐reducing effects of climate change in this region. Plain Language Summary: Nearly half of the world's deforestation occurs in the "arc of deforestation" located along the southern border of the Amazon rainforest in Brazil. While the effects of deforestation on river flows are partially understood from previous field observations and models, the regional impacts of deforestation in this area have not been quantified to date, which poses an obstacle to policy making. This study uses a large collection of historical data from ground measurements and satellites, and data analysis methods that can reveal cause and effect in complex systems, to estimate the regionally averaged effects of deforestation from 1950 to present on river flows. The results show that (1) deforestation increases river flow, specifically during the dry season; (2) deforestation increases regional average rates of flow by 4.08 km 3 /year annually; and (3) changes in temperature and rainfall that occurred at the same time as deforestation partially mask the increases in river flow that were caused by deforestation—resulting in an actual, observed flow rate increase of 2.41 km 3 /year annually. Key Points: Deforestation increases streamflow across Brazil's arc of deforestation, with significant increases to seasonal low flow Deforestation counteracts the streamflow‐reducing effects of climate change across the arc of deforestation Causal statistical analysis of hydrological data confirms the regional generalizability of prior individual basin studies